Penafsiran Quraish Shihab Tentang Pendidikan Akhlak Dalam Al-Qur’an Surat Al-Ahzab Ayat 21 Pada Tafsir Al-Misbah - Fitrah Sugiarto, Indana Ilma Ansharah (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
This paper aims to find out the interpretation of the Quraish Shihab about the education of ahklak in the Al-Quran. This needs to be conveyed considering that lately, especially in Indonesia, there are many problems, one of which is an acute problem of morality and needs to be resolved in stages. Many of the criminal cases that have occurred lately are due partly to moral degradation. Indonesian people who are known as religious communities should be able to work together in grounding moral education in accordance with the teachings of the Al-Qur'an as explained by the Quraish Shihab in the Book of Tafsir Al-Misbah. Quraish Shihab, which has an interpretation of the Adabi Ijtima'i style, is expected to be able to provide insight into current moral education. This study used a qualitative descriptive method with a literature review approach. Islam wants the birth of a noble civilization that can provide broad benefits for all mankind. That is one of the goals of the Prophet Muhammad SAW to the face of this earth to perfect morals. Morals have a very important role in building a complete human civilization both physically and mentally. Quraish Shihab interpreted the QS. Al-Ahzab [33]: 21 that the verse is a form of threat to hypocrites, namely Muslims, but in their lives it does not reflect the very great and noble teachings of Islam. The point is that anyone who has embraced Islam should put forward morals in action. The glory of Islam is reflected in the morals of Rasulullah SAW, who should be able to be an example and guidance of Muslims in making mu'amalah both vertically and horizontally. That is why moral education needs to be trained from an early age, exemplified so that it can be an example and it needs the involvement of all parties in the application of moral education not only in the school environment, but in the community. It is hoped that this moral education will be able to provide solutions to the problems of moral degradation that have recently occurred in Indonesia.